Plan of the subdivision of the Castlecrag Estate, Parish of Willoughby, County of Cumberland, [3] - Greater Sydney Development Association Limited; Griffin, Walter Burley, 1876-1937 ([Sydney : Greater Sydney Development Association Limited], 1921)
Sales plans of Castlecrag estate showing the lots and subdivisions along the Edinburgh Road.
Part of the collection: Eric Milton Nicholls collection.
Condition: tear in the middle and edges folded.
Poster on verso : Castlecrag : before deciding be sure to see the finest harbour views offering in Sydney.
Corrections on poster: Milson's Point to Willoughby ; Telephone numbers J3448 to B3726
Inscriptions in pencil: DP 11138, Vol 3104 F 143 ; Lots 59 & 60 ; new lots 370-374 added in upper right corner.
Signature: Walter Burley Griffin, Landscape Architect.
Keywords: Real property -- New South Wales -- Castlecrag -- Maps; Castlecrag (N.S.W.) -- Maps